Detection of Autoantibodies against Recombinant Desmoglein 1 and 3 Molecules in Patients with Pemphigus vulgaris: Correlation with Disease Extent at the Time of Diagnosis and during Follow-Up - Anna Belloni-Fortina; Diana Faggion; Barbara Pigozzi; Andrea Peserico; Matteo Bordignon; Vincenzo Baldo; Mauro Alaibac (Clinical and Developmental Immunology)
The recent availability of cDNA clones for pemphigus antigens has allowed the production of recombinant desmoglein 1 and desmoglein 3 molecules and the development of an ELISA approach in order to determine levels of antibodies to them. The aim of the study was to determine the relationship between autoantibodies levels and the extent of both mucosal and skin lesions in 20 patients with pemphigus vulgaris at the time of diagnosis and during follow-up. For the detection of autoantibodies by ELISA we used the recombinant proteins expressing overlapping sequences with the entire extracellular desmoglein 1 and desmoglein 3 domains. We showed that in presence of mucosal lesions there was a correlation between extension of mucosal involvement and autoantiboidies titres against both desmoglein 1 and desmoglein 3, whereas in presence of skin lesions there was a statistically significant correlation between extension of skin lesions and autoantibodies titres against desmoglein 3, but not against desmoglein 1. A not negligible number of patients showed variations of the desmoglein 3 autoantibodies titre which did not correlate with the severity of both cutaneous and mucosal involvement. Similar results were obtained analyzing autoantibodies titres against desmoglein 1. In conclusion, we believe that the utilization of recombinant desmoglein 1 and desmoglein 3 proteins by ELISA should be used with caution to monitor disease severity and response to therapy, although it remains a high specific test for the initial diagnosis of pemphigus and the identification of a change in the clinical phenotype of this condition.